Hysterectomy Past, Present and Future - Odeh Amarin, Zouhair (IntechOpen, 2022)
Hysterectomy is a common gynaecological procedure. This book presents a comprehensive overview of this surgery, including a brief history of the procedure, the different techniques used, how to choose the appropriate method, and potential complications.